2012
DOI: 10.3389/fendo.2012.00113
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role for adenosine and its receptors in bone homeostasis

Abstract: Bone is continually being remodeled and defects in the processes involved lead to bone diseases. Many regulatory factors are known to influence remodeling but other mechanisms, hitherto unknown, may also be involved. Importantly, our understanding of these currently unknown mechanisms may lead to important new therapies for bone disease. It is accepted that purinergic signaling is involved in bone, and our knowledge of this area has increased significantly over the last 15 years, although most of the published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 80 publications
(106 reference statements)
2
44
0
Order By: Relevance
“…Bone remodeling requires a constant supply of energy; adenosine, the metabolite generated by the breakdown of extracellular nucleotide molecules such as ATP, accumulates under conditions of cellular stress or altered metabolism such as bone fracture and bone repair (Mediero and Cronstein, 2013;Bowler et al, 2001;Orriss et al, 2010;Ham and Evans, 2012). In a previous study, we investigated the differential expression of genes by RANKL treatment during osteoclast differentiation by screening the cDNA microarray data; we found that Adora2b was induced after 24 hours of RANKL treatment (Kim and Lee, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone remodeling requires a constant supply of energy; adenosine, the metabolite generated by the breakdown of extracellular nucleotide molecules such as ATP, accumulates under conditions of cellular stress or altered metabolism such as bone fracture and bone repair (Mediero and Cronstein, 2013;Bowler et al, 2001;Orriss et al, 2010;Ham and Evans, 2012). In a previous study, we investigated the differential expression of genes by RANKL treatment during osteoclast differentiation by screening the cDNA microarray data; we found that Adora2b was induced after 24 hours of RANKL treatment (Kim and Lee, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of A2AR, A2BAR and A3R inhibits osteoclast differentiation and function, whereas A1R stimulates it (Mediero and Cronstein, 2013;Orriss et al, 2010;Ham and Evans, 2012;Kara et al, 2010). A2BAR stimulation by its specific agonist BAY 60-6583 promotes osteoblast differentiation through modulation of Runx2 and Osterix levels and decreases osteoclast differentiation (Corciulo et al, 2016;Carroll et al, 2012;Trincavelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Original Article -328 -and osteoarthritis (Rodan and Martin, 2000), and, when bones are fractured or repair, the production of adenosine is enhanced from increased extracellular nucleotide molecules such as ATP (Ham and Evans, 2012;Mediero and Cronstein, 2013;Kim et al, 2017). There are four adenosine receptors (A1R, A2AR, A2BAR and A3R) that are members of the G protein-coupled receptor family.…”
Section: The Increase Of Proliferation And/or Activity Of Osteoclastsmentioning
confidence: 99%
“…There are four adenosine receptors (A1R, A2AR, A2BAR and A3R) that are members of the G protein-coupled receptor family. Although all of adenosine receptors are expressed in osteoblasts and osteoclasts, they show the different biological actions (Orriss et al, 2010;Ham and Evans, 2012;Mediero and Cronstein, 2013). Among them, whereas A2BAR stimulation with its specific agonist BAY 60-6583 decreases osteoclast differentiation, it increases osteoblast differentiation (Carroll et al, 2012;Trincavelli et al, 2014;Corciulo et al, 2016;Kim et al, 2017).…”
Section: The Increase Of Proliferation And/or Activity Of Osteoclastsmentioning
confidence: 99%
“…Taken together, these results support the role of A2BR in osteoblast differentiation, but the downstream signaling following A2BR activation remains unclear. However, it is known that A2BR signaling is coupled to the activation of cyclic AMP through a Gs protein [83], and this is supported by Hsiae et al who engineered a GPCR with a constitutively active Gs signal and found this dramatically enhanced bone mass [84]. In contrast, a recent study by Hajjawi et al demonstrated osteoblast numbers are unaffected by supraphysiological concentrations of adenosine or an A2B agonist (BAY606583).…”
Section: P1 Receptors: A2brmentioning
confidence: 99%